Strategi Membangun Kepuasan Pelanggan melalui Mutu Pelayanan pada CV Cokro 2000 - Eduart Wolok (Jurusan Manajemen Fakultas Ekonomi dan Bisnis Universitas Brawijaya, 2012)
The research is how is the Strategy in supporting customer satisfaction through service quality at CV. Cokro 2000 that engaged in business sales of Honda Motorcycle in credit. The method in this research was qualitative method with phenomenology approach. So the researher’s role was as main instrument that directly involved in collecting the data through observation and interview. Therefore, the data was accurate according with the research needed. Data analyzed in this research was SWOT analysis. Those are strengths, weakness, opportunities and threats. Based on the research result and data analysis, it can be concluded that the Strategy in supporting customer satisfaction through service quality that developed by CV. Cokro 2000 is based on the strategy concept of service quality to attract the customer so that their stuff are in demand. In addition, the customer feel satisfy with the stuff of CV. Cokro 2000. It’s engaged in Honda Motorcycle selling by credit system. Fund in CV. Cokro 2000 is got from FIF (Federal International Finence). FIF gave fund such Honda motorcycles and CV Cokro 2000 run the effort with good service strategy.Keywords: Strategy, Satisfaction, Service, CV Cokro, Business.